(untitled) (Vietnam Journal of Community Medicine, 2022)
This study aims to validate seeking and using health information questionnaires for mothers with children under 1 year old in Hanoi 2019. The questionnares developed and referenced based on two questionnaires of Yen-Yuan Chen, PSM (the online academic help-seeking questionnaire) and OIMH (Online Health Information Utilization questionnaires). The cross-section study was conducted with 301 mothers taking their children for vaccination at 3 vaccination centers in Hanoi. The average age of mothers in this study was 31.18; the reliability coefficient (Cronbach Alpha) of each question is from 0.62 to 0.86; all variables are retained in the questionnaires; KMO test reached 0.81, and Barlett’s test has p<0.05, indicating that this questionnaire is suitable for factor analysis (EFA); EFA analysis produced 7 groups of factors; structural equation modeling (SEM) was performed to confirm the appropriate structure of the questionnaires for the mothers with children under 1 year of age: RMSEA = 0.076, SRMR = 0.07, TLI = 0.81, CFI = 0.84. These results have shown that the structure of seeking and using health information questionnaires is reliable and appropriate. Therefore, other studies have a scientific basis for using this questionnare to evaluate the search and use health information for mothers with children under 1 year of age.